Pengaruh Interest Rate, Capital Adequacy Ratio, Dan Non Performing Loan Terhadap Return On Asset Lembaga Perkreditan Desa - I Made Aribawa; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the effect of interest rates, capital adequacy ratios, and non-performing loans on return on assets. This type of research is quantitative by using instruments in its measurement and statistical management. This research was conducted in Bangli District. The population in this study were all LPD in Bangli District with a total of 23 LPD. The financial statements that will be examined are in 2018-2021 or for four years, so that the total population in this study totals 92 reports. Determination of the sample using the total sampling method, so that a sample of 72 was obtained. The research data was obtained directly at the LPLPD in Bangli Regency which was then processed using multiple linear regression analysis tests with the help of SPSS 25.The results of the study show that interest rates and non-performing loans have a significant negative effect on return on assets, and the capital adequacy ratio has a significant positive effect on return on assets.